(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of this paper is to introduce a new type of fuzzy generalized mappings namely \(fgspr\)-closed mappings, \(fgspr\)-open mappings, \(fgspr^*\)-closed mappings and \(fgspr^*\)-open mappings in fuzzy topological spaces and study some of their properties.